Removal of nutrients from water column and physiological responses of Vallisneria natans under sulfonamide stress. Issue 1 (1st January 2019) - Xu, Houtao; Zhu, Liming; Wang, Liqing; Zheng, Xiaoyan; Cao, Linkui
Abstract: For a better understanding of the metabolic adaptations to sulfonamide (SA) stress in submerged macrophytes, the alterations of nutrient element uptake and secondary metabolism were studied in the leaves of Vallisneria natans (Lour.) Hara exposed to 0 and 50 mg/L of SA for 15 d. The results showed that, under a treatment of 50 mg/L SA, the malondialdehyde and superoxide anion (O2 − ) contents in V. natans leaves significantly increased, 1.77–3.32 times higher than the control group, respectively, while the chlorophyll concentration showed a 36.99% reduction at the end of experiment. Simultaneously, V. natans showed a removal effect on SA and SA dramatically affected the nutrient removal efficiency by V. natans . Our results suggest that high SA levels can damage V. natans tissue and in turn that results in a stimulation of the antioxidant response. V. natans significantly improved the removal efficiency of SA, meanwhile SA resulted in less removal of TN and TP from the water column.